(untitled) (Global Journal of Science Frontier Research, 2025)
The aim of this work on DM is to confine it whether it belongs to the dark periodic table or is part of a single very small dark element as mentioned in [10] making it possible to improve the works presented by the undersigned in the bibliography for example teleportation [7] could be improved with elements inserted in a certain way from the dark periodic table: in the W spiral of the classical periodic table, or in the antigravity ’ Poynting vector’ in fig. 3 [5].